Edge‐Grafted Molecular Junctions between Graphene Nanoplatelets: Applied Chemistry to Enhance Heat Transfer in Nanomaterials. (25th January 2018) - Bernal, Maria Mar; Di Pierro, Alessandro; Novara, Chiara; Giorgis, Fabrizio; Mortazavi, Bohayra; Saracco, Guido; Fina, Alberto
Abstract: The edge‐functionalization of graphene nanoplatelets (GnP) is carried out exploiting diazonium chemistry, aiming at the synthesis of edge decorated nanoparticles to be used as building blocks in the preparation of engineered nanostructured materials for enhanced heat transfer. Indeed, both phenol functionalized and dianiline‐bridged GnP (GnP‐OH and E‐GnP, respectively) are assembled in nanopapers exploiting the formation of non‐covalent and covalent molecular junctions, respectively. Molecular dynamics allow to estimate the thermal conductance for the two different types of molecular junctions, suggesting a factor 6 between conductance of covalent vs noncovalent junctions. Furthermore, the chemical functionalization is observed to drive the self‐organization of the nanoflakes into the nanopapers, leading to a 20% enhancement of the thermal conductivity for GnP‐OH and E‐GnP while the cross‐plane thermal conductivity is boosted by 190% in the case of E‐GnP. The application of chemical functionalization to the engineering of contact resistance in nanoparticles networks is therefore validated as a fascinating route for the enhancement of heat exchange efficiency on nanoparticle networks, with great potential impact in low‐temperature heat exchange and recovery applications. Abstract : Edge‐functionalized graphene nanoplatelets (GnP) are assembled in nanopapers exploiting the formation of molecular junctions between nanoflakes for the enhancement of the thermal boundary conductance. The cross‐plane thermal conductivity of functionalized GnP nanopapers is dramatically enhanced by 190%. The edge‐selective functionalization is validated as a fascinating route for the enhancement of heat exchange efficiency on GnP networks.